AB0656 Serum vitamin d and parathyroid hormone levels in premenopausal women with fibromyalgia syndrome. (23rd January 2014) - Balkarli, A.; Balkarlı, H.; Temel, S.; Ozhan, N.; Ozkan, U.; Cobankara, V.
Abstract : Background: Fibromyalgia syndrome (FMS) is a common chronic musculoskeletal disorder characterized by the presence of widespread pain and multiple tender points on physical examination. Deficiency of vitamin D can cause similar musculoskeletal symptoms. Studies regarding vitamin D and FMS relationship have been done in the recent years. Although some studies determined this relationship, other have failed to do so. Objectives: We aimed to evaluate the relationship between serum vitamin D and parathyroid hormone (PTH) levels and clinical findings in premenopausal FMS patients. Methods: 77 patients diagnosed with FMS according to new criteria and 60 healthy women were included in this study. We did not include smokers and obese patients. Both groups were questioned for age, height, weight, BMI, education level, working status, number of children, menarche age, living condition (urban, rural), dressing style and sun exposure. Both groups were checked for serum calcium, phosphor, alkaline phosphatase, vitamin D, and PTH levels. FMS new diagnosis criteria scoring, sleep symptom scale, SF-36, Beck depression scale, BASDAI, VAS, revised fibromyalgia impact (FIQR) questionnaires were done to the patient group, and scores were recorded. Serum vitamin D deficiency was described as ≤20 ng/mL, insufficient vitamin D as 21-29 ng/mL and adequate vitamin D as ≥30 ng/mL. Results: Mean age was 38, 68±5, 196 and 38, 12±4.939 years for patient and control group, respectively. No significant difference was found between the groups for age, height, weight, BMI, education level, working status, number of children, menarche age, living condition (urban, rural), dressing style and sun exposure (p>0.05). Hemoglobin, calcium, phosphor, and alkaline phosphatase were similar in both groups. Serum vitamin D levels were found lower in the patient group when compared with controls (p=0.000). Parathyroid hormone levels were significantly higher in the patient group (p=0.000). Vitamin D levels were ≤20 ng/mL for 32 (42.7%), 21-29 ng/mL for 14 (18.7%) and >30 ng/mL for 29 (38.7) patients. No significant difference between scores were found when patients who had serum vitamin D levels ≤20 ng/mL and >20 ng/mL compared. SF-36, new diagnosis criteria score and FIQR scores were correlated. Patient serum PTH levels and serum vitamin D levels showed negative correlation, and it was significantly higher than in the control group (p=0.000). Conclusions: We determined an increase in vitamin D deficiency and insufficiency in FMS patients. However, pain and quality of life scores did now show any significant difference when patient who had vitamin D deficiency and patients who did not have were compared. We highly think that receptor inactivity must be investigated before stating that vitamin D levels and FMS disease scores do not show any correlation. Disclosure of Interest: None Declared